Why do employees have better family lives when they are highly engaged at work? - Ilies, R.; Liu, X.; Liu, Yukun; Zheng, X. (American Psychological Association, 2017)
Past research on the effects of work engagement on the family has demonstrated contrasting effects, with some suggesting that work engagement is beneficial for family life whereas others suggesting that it may be detrimental. In this research, using a sample of 125 employees who responded to daily surveys both at work and at home for 2 consecutive weeks, the authors present a multilevel examination of the relationships of work engagement to family outcomes aimed at elucidating such work–family effects. Their findings revealed that employees’ daily work engagement experiences related positively, within individuals, to work–family interpersonal capitalization, which in turn, related positively to daily family satisfaction and to daily work–family balance. The findings also indicate that both the relationship between daily work engagement and work–family interpersonal capitalization and the indirect effects of daily work engagement on the family outcomes were stronger for employees with higher intrinsic motivation than for those with lower intrinsic motivation. The authors discuss theoretical and practical implications of the findings and offer directions for future research.